Interactions Mechanism of Commonly Used Drugs for the Treatment of COVID-19 - Çelik, Sefa; Demirağ, A. Demet; Özel, Ayşen E.; AKYÜZ, SEVİM (Bulletin of the Chemical Society of Ethiopia, 2020)
In this study conformation analysis of seven drugs commonly used in the treatment of COVID-19 was performed. The most stable conformers of the drug molecules were used as initial data for docking analysis. Using the Cavityplus program, the probable most active binding sites of both apo and holo forms of COVID-19 main protease enzyme (M-P(ro)) and spike glycoprotein of SARSCoV-2 receptors were determined. The interaction mechanisms of the 7 FDA approved drugs (arbidol, colchicine, dexamethasone, favipiravir, galidesivir, hydroxychloroquine, remdesivir) were examined using the AutoDock Vina program. The six of the seven drugs were found to be more stable in binding to apo form of COVID-19 M-P(ro) and spike glycoprotein. Moreover, a set of molecular mechanics (MM) Poisson-Boltzmann (PB) surface area (SA) calculations on the investigated drugs-protein systems were performed and the estimated binding free energy of remdesivir and the apo form of MP' system was found to be the best. The interaction results of FDA drugs with the apo form of COVID-19 M-P(ro) and spike glycoprotein can play an important role for the treatment of COVID-19.
Keywords: COVID-19; Drugs; Molecular Modelling; Conformational Analysis; Molecular Docking